Étudier les circuits courts par les traces numériques de leurs réseaux - Raphaël Stephens (EchoGéo)
Digital platforms and digital traces which reconfigure local and Alternative Food Networks (AFNs) provide important possibilities for the structural analysis of their networks. This article studies the structure of the network of local food platform La Ruche qui dit Oui ! through digital data on the interactions between its producers and its distribution points. A graph analysis method mobilizing tools from the CorText Platform helps identify exploratory results characterized by unequal relations within the network. Links are thus revealed between (i) the degree of network integration of distributors relative to their geographic centrality-periphery and local socioeconomic characteristics, and (ii) the degree of network integration of suppliers according to the agricultural or processed nature of the foods they commercialize.